Interior design since 1900 - Massey, Anne, 1956- (Thames and Hudson, 2020)
A one-volume guide to the world's most iconic and important interiors, from William Morris's home in London to the retail and leisure spaces of the contemporary globalized world.
Keywords: Interior decoration -- History -- 20th century.; 1900-1999; elektronické knihy; electronic books